Multiple liver metastases of pulmonary carcinoid successfully treated by two-stage hepatectomy combined with embolization of portal vein branches: Report of a case. (2020) - Kamada, Teppei; Onda, Shinji; Takano, Yuki; Sakamoto, Taro; Kikuchi, Ryo; Yanaga, Katsuhiko
Highlights: The prognosis of atypical pulmonary carcinoid with liver metastases is poor, and the patients are often treated using non-surgical therapies. We successfully treated multiple liver metastases from atypical pulmonary carcinoid by using two-stage hepatectomy combined with embolization of portal vein branches. Two-stage hepatectomy may be a good option for bilobar multiple liver metastases of atypical pulmonary carcinoid. Abstract: Introduction: The prognosis of atypical pulmonary carcinoid with liver metastases is extremely poor, and patients with multiple liver metastases are often treated using non-surgical therapies. We report a case with multiple liver metastases from atypical pulmonary carcinoid that was successfully treated using two-stage hepatectomy combined with embolization of portal vein branches. Presentation of case: A 48-year-old man was referred to our department after multiple liver tumors were detected in both liver lobes on computed tomography. He had undergone right upper lobectomy of the lung for atypical pulmonary carcinoid (T2a, N0, M0; Stage IB) 2 years previously. Positron emission tomography-computed tomography showed no extrahepatic tumor manifestations. The tumors were located in segment 2, 3, 5/8 and the right hepatic vein drainage area. We planned complete resection of metastases in a two-stage hepatectomy. The first stage comprised concomitant left lateral segmentectomy, partial hepatectomy of segment 5/8 and portal vein embolization of the posterior segmental branches. The second stage comprised resection of the right hepatic vein drainage area, performed 21 days after the first surgery. Histopathological diagnosis was liver metastases of atypical pulmonary carcinoid. Postoperative bile leak developed, which was treated with endoscopic retrograde biliary drainage and percutaneous bile leak drainage. He has been followed for 24 months postoperatively without tumor recurrence. Discussion: Two-stage hepatectomy may represent an option for bilobar multiple liver metastases from atypical pulmonary carcinoid. Conclusion: We successfully treated a patient with multiple liver metastases of atypical pulmonary carcinoid using a two-stage hepatectomy combined with portal vein embolization of the posterior segmental branches.